Answer:
See explanation
Explanation:
Zeros of the function are those values of x, for which g(x)=0, so solve the equation g(x)=0:
![x^3-x^2-4x+4=0\\ \\x^2(x-1)-4(x-1)=0\\ \\(x-1)(x^2-4)=0\\ \\(x-1)(x-2)(x+2)=0\\ \\x_1=-2,\ x_2=1,\ x_3=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yo3tbbmzmw680lis7upelpc24cwantbvni.png)
Hence, the function has three zeros, x=-2, x=1 and x=2.
To find the y-intercept, substitute x=0:
![y=g(0)=0^3-0^2-4\cdot 0+4=4,](https://img.qammunity.org/2020/formulas/mathematics/middle-school/44a6ly0zk2jbefwbk6qz05fw0e8kd7bqz6.png)
so y-intercept is at point (0,4).
The graph of the function shows that when x is infinitely small, then y is infinitely small too and if x is infinitely large, then y is infinitely large too.